Effect of Nonlinear Thermal Radiation, Heat Source on MHD 3D Darcy-Forchheimer Flow of Nanofluid Over Aa Porous Medium with Chemical Reaction - Tarakaramu, Nainaru; Ramesh Babu, K.; V. Satyanarayana, P. (International Journal of Engineering and Technology, 2018)
The present work nonlinear thermal radiation and chemical reaction effect on three-dimensional MHD flow of permeable medium analysed. We are considering introduce the Darcy-Forchheimer law along with axial and transverse velocity. Using suitable transportations the nonlinear partial differential equations are converted into ordinary differential equations. These equations are solved numerically by 4th Runge-Kutta-Fehlberg scheme with shooting procedure. We are getting unique numerical solution for distinct physical variables temperature and concentration fields are depicted. Also the heat transfer and skin friction coefficients drawn through numerical data. We are finding great results of the velocity profiles behaviors opposite trend of porosity and Forchheimer parameters, the profiles of and behavior reverse trend follows other than chemical reaction parameter, both directions of skin friction coefficient and heat transfer rates reduction.Â Â